Social Change, Astro-Turfs, and Entrepreneurial Activities in the Context of German Non-Elite Football: The Example of Lower-Division Club BSV Bielstein. Issue 7 (24th May 2018) - Naglo, Kristian
Abstract: This article explores the efforts of a German non-elite football club to revitalize itself using a combination of modernization strategies to overcome a perceived existential crisis. The modernizing strategies involved improving facilities (laying an artificial pitch and building a new club house) while at the same time actively pursuing a community role via, for example, work with refugees. The interdisciplinary approach used here stresses the peculiar character of institutionalization/bureaucratization (clubs/associations) in combination with the social world of club football as emotional community in Germany since the nineteenth century. In contrast to an emphasis on the systemic character of football as a closed social system with its specific set of rules in which the logic of action is historically predetermined, this article focusses on social actors and their constant struggle to recreate and redefine the social world of football through their actions.